MODEL INTENSI KEWIRAUSAHAAN DENGAN PERTIMBANGAN PASAR KERJA, DUKUNGAN SOSIAL, DAN SELF EFFICACY TERHADAP PENGAMBILAN KEPUTUSAN KARIR - Nurhidayati Nurhidayati; Dyan Tri Utari (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to determine and analyze the effects of labor market considerations, socialsupport and self efficacy against student entrepreneurial intentions and their impact on careerdecision making. The population used is a student of Islamic University of Sultan AgungSemarang consisting of 6 Faculties of 16,885 people, with a sample size of 100 respondents.The sampling technique is purposive sampling. The analysis tool is multiple linear regression,where previously tested the validity and reliability as well as the classical assumption test.The test results indicate that labor market consideration of entrepreneurial intention showsnegative influence, it can be interpreted that the bigger the consideration of job market, hencethe opportunity of job availability also bigger so that will decrease intention of student to doentrepreneurship. Social support and self efficacy have a positive effect on entrepreneurialintention. Intentional entrepreneurship proved to have a negative influence on career decisionmaking, can be interpreted that the higher the intention of students with a supported matureplan in entrepreneurship, it will further lower students in decision making for a career.Keywords: Job market considerations, social support, self efficacy, intense entrepreneurshipand career decisions